Potatoes from seed - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
The International Potato Center (CIP) in Lima, Peru, has been developing seed potatoes derived from 'true potato seed' (TPS) that can be produced in a nursery. Potatoes are normally grown from 'seed potatoes', which are not seeds but tubers and are...